2023
DOI: 10.3390/jpm13030448
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cystic Fibrosis Research in Qatar: A Commentary

Abstract: Cystic fibrosis is a genetic disorder caused by a Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene defect. Many across the globe suffer the debilitating symptoms. The aim of this commentary is to briefly cover various aspects related to the disease in the Arab world and then in Qatar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The same trend is observed in Asia; CF is more prevalent in West Asia compared with East Asia. [2][3][4][5] Obtaining accurate statistics on the prevalence of a certain disease in Iran is challenging due to the lack of a comprehensive registration system, the limited availability of diagnostic tests, and the economic and social conditions in certain areas. 6 Recent studies have shown that this disease is more common among children under the age of 18 in Iran than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend is observed in Asia; CF is more prevalent in West Asia compared with East Asia. [2][3][4][5] Obtaining accurate statistics on the prevalence of a certain disease in Iran is challenging due to the lack of a comprehensive registration system, the limited availability of diagnostic tests, and the economic and social conditions in certain areas. 6 Recent studies have shown that this disease is more common among children under the age of 18 in Iran than previously thought.…”
Section: Introductionmentioning
confidence: 99%